Kotransplants based on hepatocytes and mesenchimal stem cells: characteristic, clinical application and primary assessment of the approach efficiency - Symanovich, Ala A.; Prymakova, Yauheniya A.; Homan, Anastasiya A.; Dzyadzyulya, Natallya I.; Piatrouskaya, Katsiaryna G.; Buzuk, Evgenia S.; Smol’nikova, Victoria V.; Shcherba, Aliaksei E.; Krivenko, Svetlana I. (Journal of the Belarusian State University. Ecology, 2019)
The results of a study on the effect of co-cultivation of mesenchymal stem cells isolated from adipose tissue and hepatogenic differentiation’ mesenchymal stem cells on the viability and functional activity of hepatocytes in a coculture are presented. It was established that a high level of secretion of liver proteins by differentiated mesenchymal stem cells and providing them with functional and metabolic properties of isolated hepatocytes was observed in the first days of cultivation (HGF (p = 0.06) and ANGPTL4 (p
Keywords: hepatocytes; mesenchymal stem cells; hepatocyte-like cells; co-culture; the level of liver secretory soluble proteins; morphological characteristics; cell co-transplantation